The A3 Redox-Neutral C1-Alkynylation of Tetrahydroisoquinolines: A Comparative Study between Visible Light Photocatalysis and Transition-Metal Catalysis - Ortiz Villamizar, Marlyn C.; Puerto Galvis, Carlos E.; Kouznetsov, Vladimir V. (Synthesis, 2020)
Considering the current challenges of the A3 redox-neutral C1-alkynylation of tetrahydroisoquinolines (THIQs), we studied this synthetic tool under visible light photocatalysis and transition-metal catalysis in order to describe alternative reaction conditions and discuss possible improvements to this process. We demonstrated that 1-alkynylated THIQs can be readily obtained by three different approaches: iridium-based photocatalysis and copper ([CuBr(PPh3)3]) and silver (AgNO3) catalysis under mild, selective and accessible reaction conditions. Among these approaches, the copper(I)-based methodology resulted in the most robust, optimal reaction conditions for the synthesis of a series of 18 1-alkynylated THIQs in moderate to excellent yields and with high selectivity for the endo-alkynylated products. Moreover, this reaction can be accelerated by microwave irradiation (120 °C, 15 min) affording a novel library of diverse THIQs with alkyne and N-substituent moieties, from unreactive and uncommon substrates, that could be further transformed into new compounds of interest.
Keywords: A3 coupling reaction; C1-alkynylation; tetrahydroisoquinolines; photocatalysis; transition-metal catalysis